The case of character education implementation in elementary schools: How are promotions and its problems? - Dedy Irawan; Yuli Windarti (International Journal of Education, Vocational and Social Science, 2023)
Nowadays, the attitude and behaviour of Indonesian students are declining. As a character-building component, schools have an important task in instilling morals, ethical values, noble morals, and strong and resilient character. This study was conducted to analyse the implementation of character education at SD Negeri 2 Pengadegan. Qualitative research with an ethnographic approach was used in this study on implementing character education in elementary schools during one semester of 2021/2022. A total of 20 participants were interviewed, including principals, teachers, parents and students. Observation, interviews and documentation were used as research instruments. Character education promotion implemented at SD Negeri 2 Pengadegan covers 20 aspects. This research describes the character education strategies: exemplary habituation, school climate conditioning, integration in all subjects, and integration through extracurricular activities. Good cooperation from all school members is a supporting factor for character education at SD Negeri 2 Pengadegan. However, character education is hampered by the lack of parental concern at home and the negative response of some parents to the enforcement of school regulations. To overcome this, schools should improve communication with parents.